A Regulatable Data Privacy Protection Scheme for Energy Transactions Based on Consortium Blockchain. (7th December 2021) - Li, Yufeng; Chen, Yuling; Li, Tao; Ren, Xiaojun
Abstract : In the blockchain-based energy transaction scenario, the decentralization and transparency of the ledger will cause the users' transaction details to be disclosed to all participants. Attackers can use data mining algorithms to obtain and analyze users' private data, which will lead to the disclosure of transaction information. Simultaneously, it is also necessary for regulatory authorities to implement effective supervision of private data. Therefore, we propose a supervisable energy transaction data privacy protection scheme, which aims to trade off the supervision of energy transaction data by the supervisory authority and the privacy protection of transaction data. First, the concealment of the transaction amount is realized by Pedersen commitment and Bulletproof range proof. Next, the combination of ElGamal encryption and zero-knowledge proof technology ensures the authenticity of audit tickets, which allows regulators to achieve reliable supervision of the transaction privacy data without opening the commitment. Finally, the multibase decomposition method is used to improve the decryption efficiency of the supervisor. Experiments and security analysis show that the scheme can well satisfy transaction privacy and auditability.